2015
DOI: 10.1177/2158244015602045
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Risk Factors for Single and Recurrent Falls Among the Community-Dwelling Elderly

Abstract: The purpose of this study was to identify gender differences in risk factors of fall accidents among older people, and whether these factors differ between single and recurrent fallers. A total of 4,426 individuals aged ≥65 years from two large-scale health surveys provided data. Logistic regression analyses were used to identify risk factors and to determine the risk model for falling and recurrent falling in men and women separately. Three major risk factors for falling regardless of gender or fall history a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…The prevalence of falls varies among different regions of the world. While we found a percentage of 29.3% of falls during the last year, a study conducted in Amsterdam found a result of 34% (Yu & El Fakiri, 2015), and a Chinese study found 14.1% (Chu, Chiu, & Chi, 2008). These differences may be due to population characteristics, such as behavior, culture, and environmental aspects as previous studies indicate that Asian elders are more physically active than other older adult populations (Hallal et al, 2012).…”
Section: Discussioncontrasting
confidence: 73%
“…The prevalence of falls varies among different regions of the world. While we found a percentage of 29.3% of falls during the last year, a study conducted in Amsterdam found a result of 34% (Yu & El Fakiri, 2015), and a Chinese study found 14.1% (Chu, Chiu, & Chi, 2008). These differences may be due to population characteristics, such as behavior, culture, and environmental aspects as previous studies indicate that Asian elders are more physically active than other older adult populations (Hallal et al, 2012).…”
Section: Discussioncontrasting
confidence: 73%
“…Especially in those who experience repeated falls, this limitation becomes more apparent, and they have to cope with the fear of falling. 3 Therefore, it is necessary to assess both falls and the fear of falling in older adults. 4 Fear of falling was initially evaluated only by revealing whether individuals were concerned of falling.…”
Section: Validity and Reliability Of The Iconographical Falls Efficac...mentioning
confidence: 99%
“…All these possibilities lead older adults to develop a fear of falling, which they try to reduce by restricting their activities. Especially in those who experience repeated falls, this limitation becomes more apparent, and they have to cope with the fear of falling 3. Therefore, it is necessary to assess both falls and the fear of falling in older adults 4…”
mentioning
confidence: 99%
“…The prevalence of certain risk factors [e.g., depression (Girgus et al, 2017), dementia (van der Flier & Scheltens, 2005), stroke (Appelros et al, 2009), binge drinking (Blazer & Wu, 2009), diabetes (Andes et al, 2019), and difficulty performing activities of daily living (ADL) (Liang J. et al, 2008)] differ by age and sex in the older adult population. The strength of association of falls with some risk factors [e.g., ADLs (O & El Fakiri, 2015), alcohol consumption (Chang & Do, 2015;O & El Fakiri, 2015), depression (Gale et al, 2016;Gale et al, 2018), and balance (Gale et al, 2016(Gale et al, , 2018] differs by sex. The number of co-morbidities increase with age (Vogeli et al, 2007), and some diseases cluster together more often than others (Bhattacharjee et al, 2017;Sinnige J. et al, 2013).…”
Section: Introductionmentioning
confidence: 99%